Japan Journal of Industrial and Applied Mathematics - Okamoto, Hisashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Japan Journal of Industrial and Applied Mathematics (JJIAM) is intended to provide an international forum for the expression of new ideas, as well as a site for the presentation of original research in various fields of the mathematical sciences. Consequently the most welcome types of articles are those which provide new insights into and methods for mathematical structures of various phenomena in the natural, social and industrial sciences, those which link real-world phenomena and mathematics through modeling and analysis, and those which impact the development of the mathematical sciences. The scope of the journal covers applied mathematical analysis, computational techniques and industrial mathematics.
Keywords: Applied mathematics; Engineering mathematics; Computer mathematics; Applications of Mathematics; Computational Mathematics and Numerical Analysis